Heavier yields from healthier seeds - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Crops thrive best when given a good start in life. For those crops which are normally propagated by seed, every effort must be made to keep pathogens at bay, at least until the crop is well-established. Obvious though this is, farmers throughout the...